Signet-ring cell carcinoma of ampulla of Vater: Contrast-enhanced ultrasound findings - Gao, Jin-Mei (The WJG Press, 2009)
Signet-ring cell carcinoma (SRCC) of ampulla of Vater is extremely uncommon, and less than 15 cases have been reported so far in literature. It mainly occurs in elderly people (median age 57 years). We report a rare case of SRCC of the ampulla of Vater in a 38-year-old woman who presented with a small tumor at the Vater, discovered by the contrast-enhanced ultrasound (CEUS). Histopathological examination showed prominent signet-ring features. We also describe the imaging features of SRCC of ampulla of Vater in CEUS.